Effects of irrigation frequency on growth and yields of Taraxacum kok-saghyz Rodin - G. Shen; F. Zheng; L. Zhou; X. Zeng; N. G. Konkova (Труды по прикладной ботанике, генетике и селекции)
Taraxacum kok-saghyz (TKS) is one of the most promising rubber plants in the world. The question of how irrigation affects its yields and biochemical composition has not yet been studied well. The effects of irrigation frequency on the growth and yield of Taraxacum kok-saghyz were analyzed. According to the obtained results, it was established that an increase in irrigation frequency (extension of the watering interval) gradually decreased TKS rubber and total sugar yields. With the soil water content increasing from 22.8 to 38.9%, TKS rubber and sugar yields were changing in line with a cubic polynomial equation. Regular watering once every 6 days maintains soil moisture at a level above 28.0%, which makes it possible to increase the yield of Taraxacum kok-saghyz while enhancing the water-use efficiency under the conditions of Northeastern China (Harbin).